Could Externalized St. Jude Medical Riata® Lead Be a Culture Medium of a Polymicrobial Endocarditis? A Clinical Case. (15th January 2017) - Palamà, Zefferino; Trotta, Roberta; Mandurino, Cosimo; Pinto, Mariangela; Luzzi, Giovanni; Favale, Stefano
Abstract : We report the case of a man affected by polymicrobial endocarditis developed on a St. Jude Medical Riata lead with a malfunction because of the outsourcing of conductors. The patient was treated with antibiotic targeted therapy and showed different bacteria at the blood cultures and then underwent transvenous leads extraction. Vegetations were highlighted on the caval, atrial, and ventricular tracts of the Riata lead, but the cultures were all negative. The externalization of Riata lead may cause the malfunction but it could also promote bacterial colonies and vegetations. In conclusion, looking for early signs of infection is mandatory during Riata leads follow-up checks.